The pharmacokinetics and pharmacodynamics of fentanyl administered via transdermal patch in horses - Reed, Rachel A.; Berghaus, Londa J.; Reynolds, Rose M.; Holmes, Brittany T.; Krikorian, Anna M.; Sakai, Daniel M.; Ishikawa, Yushun; Knych, Heather K. (Frontiers in Pain Research, 2024)
Introduction Understanding the pharmacokinetics and pharmacodynamics of fentanyl in horses is crucial for optimizing pain management strategies in veterinary medicine. Methods Six adult horses were enrolled in a randomized crossover design. Treatments included: placebo, two 100 mcg/h patches (LDF), four 100 mcg/h patches (MDF), and six 100 mcg/h patches (HDF). Patches were in place for 72 h. Blood was obtained for fentanyl plasma concentration determination, thermal threshold, mechanical threshold, heart rate, respiratory rate, and rectal temperature were obtained prior patch placement and at multiple time points following patch placement for the following 96 h. Fentanyl plasma concentration was determined using LC-MS/MS. Data were analyzed using a generalized mixed effects model. Results Mean (range) maximum plasma concentration (Cmax), time to Cmax, and area under the curve extrapolated to infinity were 1.39 (0.82–1.82), 2.64 (1.21–4.42), 4.11 (2.78–7.12) ng/ml, 12.7 (8.0–16.0), 12.7 (8.0–16.0), 12 (8.0–16.0) h, 42.37 (27.59–55.56), 77.24 (45.62–115.06), 120.34 (100.66–150.55) h ng/ml for LDF, MDF, and HDF, respectively. There was no significant effect of treatment or time on thermal threshold, mechanical threshold, respiratory rate, or temperature (p > 0.063). There was no significant effect of treatment on heart rate (p = 0.364). There was a significant effect of time (p = 0.003) on heart rate with overall heart rates being less than baseline at 64 h. Conclusions Fentanyl administered via transdermal patch is well absorbed and well tolerated but does not result in an anti-nociceptive effect as measured by thermal and mechanical threshold at the doses studied.